Analisis Hukum Waris Adat Terhadap Pernikahan Berimpal di Suku Adat Karo (Studi di Kelurahan Padang Mas Kecamatan Kabanjahe Kabupaten Karo Sumatera Utara) - Theresia; Rosnidar Sembiring; Runtung; Maria (CV Rewang Rencang, 2025)
The marriage ceremony of the Karo tribe is a sacred ritual that must be performed before couples can participate in other traditional ceremonies, with an exogamy system that requires marriage outside the clan (berimpal marriage) but creates complexity in terms of inheritance distribution and property arrangements. This empirical juridical research in Padang Mas Village, Kabanjahe District, Karo Regency analyzes the inheritance distribution mechanism in berimpal marriages and legal protection for heirs through literature study and interviews with descriptive analysis. The research findings show that the Karo inheritance system is patriarchal in nature, granting exclusive rights to male children according to traditional customs, however its legal protection depends on local government recognition and the Karo customary system does not have positive legal force as evidenced by the Supreme Court decision that recognizes the inheritance rights of female children, while inheritance dispute resolution can be conducted through two approaches namely civil law that guarantees legal certainty and kinship system that prioritizes social harmony and maintenance of kinship relationships.